2016
DOI: 10.1098/rsbl.2016.0666
|View full text |Cite
|
Sign up to set email alerts
|

Vocal matching: the what, the why and the how

Abstract: Over the years, vocal matching has progressed beyond being an interesting behavioural phenomenon to one that now has relevance to a wide range of fields. In this review, we use birds and cetaceans to explain what vocal matching is, why animals vocally match and how vocal matching can be identified. We show that while the functional aspects of vocal matching are similar, the contexts in which matching is used can differ between taxa. Whereas vocal matching in songbirds facilitates mate attraction and the immedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 62 publications
0
49
0
Order By: Relevance
“…Evidence that song is learned mainly from territorial neighbors is two-fold: the extent of repertoire sharing with a focal male declines with increasing distance from the male ( Figure 3A ), as does the similarity of details of songs of the same song type ( Figure 3B ; Falls et al, 1982 ), and the details of song types shared between sons and fathers are less similar than song types shared between sons and males in the sons’ year of breeding ( McGregor and Krebs, 1982 ). The advantage of sharing song types with neighbors is likely related to song type matching (e.g., Falls et al, 1982 ; King and McGregor, 2016 ) in aggressive singing interactions between males. Field studies of individually marked males have shown that song learning can continue throughout life [for both production ( McGregor and Krebs, 1989 ) and discrimination ( McGregor and Avery, 1986 ) learning], with the stimulus for learning being interactions with male neighbors.…”
Section: Song Learning In Birdsmentioning
confidence: 99%
“…Evidence that song is learned mainly from territorial neighbors is two-fold: the extent of repertoire sharing with a focal male declines with increasing distance from the male ( Figure 3A ), as does the similarity of details of songs of the same song type ( Figure 3B ; Falls et al, 1982 ), and the details of song types shared between sons and fathers are less similar than song types shared between sons and males in the sons’ year of breeding ( McGregor and Krebs, 1982 ). The advantage of sharing song types with neighbors is likely related to song type matching (e.g., Falls et al, 1982 ; King and McGregor, 2016 ) in aggressive singing interactions between males. Field studies of individually marked males have shown that song learning can continue throughout life [for both production ( McGregor and Krebs, 1989 ) and discrimination ( McGregor and Avery, 1986 ) learning], with the stimulus for learning being interactions with male neighbors.…”
Section: Song Learning In Birdsmentioning
confidence: 99%
“…By comparison, female Bay Wrens do not appear to use their songs to attract mates, but instead use their songs to defend territories against conspecific females (Levin, 1996a(Levin, , 1996b. During territorial displays, male birds often match songs with neighbors (reviewed in King & MacGregor, 2016), and males often share a high proportion of songs or song types with their neighbors (Beecher, Campbell, Burt, Hill, & Nordby, 2000;Nelson, 2000;Trillo & Vehrencamp, 2005). Sharing songs with territorial neighbors may bestow several advantages, including increased reproductive success, and increased territory tenure (Beecher & Brenowitz, 2005;Beecher et al, 2000;Payne & Payne, 1997).…”
Section: Spatial Structure Of Songsmentioning
confidence: 99%
“…Birds provide a model system for studying aggressive signals because they produce diverse acoustic signals, including elaborate and variable signals that are commonplace during territorial contests (Todt & Naguib, ). Aggressive acoustic signalling behaviours in birds include song matching (King & McGregor, ), song overlapping (Helfer & Osiejuk, ), variation in song rate (Baker, Wilson, & Mennill, ), variation in trill rate and frequency bandwidth (DuBois, Nowicki, & Searcy, ), production of low‐amplitude soft songs (Searcy et al, ) and production of nonsong calls (Ballentine, Searcy, & Nowicki, ). The most well‐studied system of aggressive contest escalation to date comes from Song Sparrows, Melospiza melodia (Akçay et al, ; Searcy & Beecher, ; Searcy et al, ).…”
Section: Introductionmentioning
confidence: 99%